Missile defense in and for Europe? - Sascha Lange; Oliver Thränert (Stiftung Wissenschaft und Politik (SWP), 2007)
The United States' plan to place parts of its Missile Defense System in European countries, pursuant to bilateral agreements, has triggered a major political controversy in Germany. However, important technical and strategic questions have been left out of this discussion. For example, to what extent is Europe really at risk of a missile attack from Iran (as the U.S. claims)? How would the planned missile defense system protect Europe? (SWP Comments / SWP)
Keywords: 320